Reduction of operating process parameters turbo-prop engines AH-24 to control rating during diagnostic - Кулик, М. С.; Якименко B. B. (Proceedings of National Aviation University (archive), 1998)
Considered is the problems of reduction turbo-prop engines parameters to conditions of comparison for diagnostics purposes. The formulas of reduction for turbo-prop engines AH-24 are proposed. The article presents a result of test these formulas